Design of a swimming small soft robot for underwater applications - Chin, Chavez Zhee Ming (2024)
Traditional rigid robots, while effective in many applications, present significant challenges in environments involving human interaction or delicate objects due to their inflexible structure, which can cause damage or accidents upon collision. Additionally, rigid robots require precise control mechanisms, limiting their adaptability to unpredictable conditions. In contrast, soft robots offer a safer, more versatile alternative. Their inherent elasticity reduces the risk of injury or damage during collisions and allows them to adapt to complex environments more effectively. This study investigates the application of biological locomotion mechanisms in a soft robot designed for underwater swimming. By utilizing flexible materials like Ecoflex, PVC sheets, and plastic films, the study successfully developed a soft robot capable of actuating in water. Key findings indicate that the robot was able to swim in a straight path, with optimal performance observed at an actuation frequency of 1.33 Hz and a pump voltage of 11 V. A second prototype validated directional control, allowing the robot to turn and manoeuvre precisely. This directional control, along with linear swimming, was incorporated into a swimming algorithm controlled by three push buttons. These advances contribute to the potential for soft robots in applications such as search-and-rescue operations, underwater exploration, and water quality monitoring.